Investigating The Improvement Of Degradation Resistant With The Addition Of SDBS Anionic Surfactant To Peo Polymer - Fakhruddin, Sarmad K.; Abdulbari, Hayder A.; Ahmad Ziad, Sulaiman; Rafeeq, Hind A. (2016)
Polyethylene Oxide (PEO) is one of the most common drag reduction agents. However, its ability to reduce drag in turbulent flow decreases with the time due to the degradation of its molecules. Thus, the enhancement of its degradation resistance by the addition of Anionic surfactant is presented. The Polyethylene oxide (PEO) was used in different concentration ranges from 10 to 60 ppm and with addition of sodium dodecyl benzene sulfonate (SDBS) as the anionic surfactant with five concentrations between 100 to 500 ppm. The degradation measurements were done using rotating disk apparatus (RDA). The RDA results have shown a considerable improvement in the degradation resistance of PEO with the addition of surfactant to the polymer solution. The interaction between the polymer and the surfactant results in transferring the polymer chain from coil to straight-like body. Thus, enhance the polymer degradation resistant ability.